Measuring the oxygen content of a single oil droplet - Feng, A; Cheng, W; Compton, R (Royal Society of Chemistry, 2016)
Using toluene droplets as a model for artificial oxygen carriers, the real-time measurement of attomole oxygen contents at the individual droplet level is reported for the first time. Oxygen reduction is observed within single individual toluene droplets when they impact with an electrode held at a suitable potential. The oxygen content within single toluene droplets is quantified by referencing the reductive charge from oxygen reduction to the charge from oxidation of a ferrocene filled toluene droplet of known concentration.